Essential Oils as Potential Tools to Control Listeria Monocytogenes in Foods - Ali, Sher; Andrade, Daphne C. M.; Rezende, Vanessa T.; Aoyanagi, Micheli M. C. C.; Franco, Bruna B.; Kamimura, Eliana S.; Oliveira, Carlos A. F. (Food Science and Engineering, 2022)
Foodborne diseases are indisputable risks to human health, as they are directly affected by the consumption of food and beverages exposed to spoiling and pathogenic microorganisms. A commonly confronted issue by the food industry is the use of synthetic additives to control microbial growth on food products. Alternatively, plant essential oils (EOs) are natural compounds with antimicrobial effects against pathogens in edible and drinkable products. Based on bacteriostatic and bactericidal activities, this review describes the antimicrobial effects of plant EOs on Listeria monocytogenes, also indicating their potential applicability in different food products. Conclusively, it is determined that the Gram-positive bacteria have more susceptibilities to the EOs. In addition, the antibacterial efficacy of the EOs reported in the literature varied according to several parameters, including the seasonal harvest of plants, well-settled methodologies for extraction of EOs, experimental conditions for testing the antibacterial effect on L. monocytogenes, and matrix effects considering several types of foodstuffs. This later represents the main challenge to be addressed in future research aiming at specific applications of EOs in food products.